The Literature on Pandemics Illuminates the Presence of Trauma and the Holocaust - G.N. Rohitkumar, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2023)
The pain brought on by the virus makes German philosopher Theodor Adorno, who branded poetry as barbarous after the Holocaust, despondent. Disasters still occur, though, and literature is still debating how to handle them. We will not draw lessons from the past as the coronavirus epidemic has already killed over 500,000 lives. Cold facts that detail the number of lives lost, jobs destroyed, and economic collapse indicate how harsher reality is. The number of positive instances became a chilling term in 2020. The COVID-19 pandemic is compared to the 1918 Spanish flu, which killed millions globally, especially children and young adults. T.S. Eliot, a victim, experienced anxiety and unease during the outbreak. In The Waste Land, he used these personal concerns and fear of dying to portray the absurdity of the post-war era.
Keywords: Epidemic; Pandemic; Covid-19; Literary Fiction; Isolation; Wars and Plague